2010
DOI: 10.1039/c0ob00062k
|View full text |Cite
|
Sign up to set email alerts
|

Rauhut–Currier type homo- and heterocouplings involving nitroalkenes and nitrodienes

Abstract: Reaction of nitroalkenes or nitrodienes with methyl vinyl ketone (MVK) or acrylate in the presence of the imidazole-LiCl catalyst system provides Rauhut-Currier (vinylogous Morita-Baylis-Hillman) adducts in moderate yield. Under similar conditions (imidazole-hydroquinone), nitroalkenes and nitrodienes undergo self-dimerization to afford the Rauhut-Currier adducts in varying yields. An alternative self-dimerization-nitro group elimination pathway in the presence tricyclohexylphosphine was observed with heteroar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…[68] Ther equired nitroalkene 109 was preparedb yanitroaldol reactiono fn itroethane with aldehyde 108 and then submitted to the Nef reactionw ith Fe in the presence Scheme36. Synthesis of ketones from nitroalkanes and nitroalkenes using iron powder under acidic conditions.…”
Section: R Eductive Methodsmentioning
confidence: 99%
“…[68] Ther equired nitroalkene 109 was preparedb yanitroaldol reactiono fn itroethane with aldehyde 108 and then submitted to the Nef reactionw ith Fe in the presence Scheme36. Synthesis of ketones from nitroalkanes and nitroalkenes using iron powder under acidic conditions.…”
Section: R Eductive Methodsmentioning
confidence: 99%
“…While the dimerization of nitroalkenes follows the expected Rauhut-Currier-type mechanism, [26,27] the mechanistic pathway to conjugated enynes was still unsettled. While the dimerization of nitroalkenes follows the expected Rauhut-Currier-type mechanism, [26,27] the mechanistic pathway to conjugated enynes was still unsettled.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Furthermore, they can be subjected to other ring-closing [21,22] and coupling reactions, [23,24] or they can serve as transition metal ligands. [26] Starting from α, -unsaturated nitroalkenes 1 and 2 with proline-based catalysts, first nitroalkene dimers 3 were generated via a Rauhut-Currier-like reaction [27][28][29] (see Scheme 1 top) followed by the fragmentation to conjugated enynes. [26] Starting from α, -unsaturated nitroalkenes 1 and 2 with proline-based catalysts, first nitroalkene dimers 3 were generated via a Rauhut-Currier-like reaction [27][28][29] (see Scheme 1 top) followed by the fragmentation to conjugated enynes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Up to now, a large number of experimental studies have been reported on the RC dimerization of acrylonitrile, 7-9 vinyl ketones, 10 acrylates, 11 and nitroalkenes. 12 The cross coupling versions of the RC reaction have also been reported. [13][14][15][16][17][18][19][20] Furthermore, the enantioselective RC reactions have been studied and signicant progress has been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…12 The cross coupling versions of the RC reaction have also been reported. [13][14][15][16][17][18][19][20] Furthermore, the enantioselective RC reactions have been studied and signicant progress has been achieved. [21][22][23][24][25][26][27] Moreover, the RC reaction has been developed for the synthesis of many natural products and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%